2377. Outcomes in Patients With History of Cardiac or Vascular Disease (CV) During Treatment of Acute Bacterial Skin And Skin Structure Infection (ABSSSI) With Delafloxacin (DLX) vs. Vancomycin/Aztreonam (VAN/AZ). (26th November 2018) - Oguchi, Godson; Beasley, Richard; Lawrence, Laura; Tseng, Carol; Cammarata, Sue K
Abstract: Background: DLX, an anionic fluoroquinolone antibiotic with Gram-positive and Gram-negative activity, was recently approved for treatment of ABSSSI. Two global phase 3 ABSSSI trials (studies 302 and 303) included patients with cardiac or vascular disease. Methods: Two multicenter, double-blind, double-dummy trials of adults with ABSSSI patients randomized 1:1 to receive either DLX monotherapy or VAN 15 mg/kg (actual body weight) with AZ for 5–14 days. Study 302 used DLX 300 mg BID IV only; study 303 used DLX 300 mg BID IV for 3 days with a mandatory blinded switch to DLX 450 mg oral BID. Key endpoints were objective response at 48–72 hours with ≥20% reduction in lesion size; and Investigator assessment of outcome based on resolution of signs and symptoms at Follow-up (FU day 14) and Late Follow-up (LFU day 21–28). Results: In the two studies, 488 CV patients were randomized in United States, Europe, Latin America and Asia. 57% were male with mean age 59 years. Average erythema area at baseline was 446 cm 2 . 58% had cellulitis, 19% abscesses, 22% wound and 1% burns. Key endpoints are given in the following table. The % of CV patients with at least one treatment-related adverse event (AE) was similar for DLX (22.7%) compared with VAN/AZ (22.4%). There were 2 DLX and 5 VAN/AZ-treated CV patients discontinued due to related AEs. The most frequent treatment-related AEs were gastrointestinal including diarrhea seen in 8.2% and 3.1% of DLX and VAN/AZ patients respectively, generally mild to moderate in nature with no cases of C. difficile diarrhea. There were no cardiac events or deaths attributed to either study drug. Conclusion: In CV patients, fixed dose DLX monotherapy was comparable to VAN/AZ in treatment of ABSSSI based on the early objective and investigator assessed responses at FU and LFU. DLX was also comparable to VAN/AZ in treating patients with S. aureus . There were no cardiac events or deaths in either study group. DLX appears effective and well tolerated in CV patients with ABSSSI. Disclosures: G. Oguchi, Melinta Therapeutics, Inc.: Investigator, Research support. R. Beasley, Melinta Therapeutics, Inc.: Investigator, Research support. L. Lawrence, Melinta Therapeutics, Inc.: Employee and Shareholder, Salary. C. Tseng, Melinta Therapeutics, Inc.: Consultant and Research Contractor, Consulting fee. S. K. Cammarata, Melinta Therapeutics, Inc.: Employee, Salary.